TERM OF THE PATENT. PREMISES FOR THE CREATION OF THE SUPPLEMENTARY PROTECTION CERTIFICATE - BUCURA IONESCU (Challenges of the Knowledge Society)
The legal nature of the rights derived from the patent was object of numerous theories and discussions in literature. Their main features represent recognized characteristics for the property right, nevertheless the limitation in time, in space and the ubiquity make the difference. Especially for new medicinal or plant protection products, due to the limitation in time, the period of effective protection under the patent is insufficient to cover the investment put into the research. There exists a risk of research centres situated in the Member States relocating to countries that offer greater protection. The uniform solution at Community level was created in form of regulations, as the most appropriate legal instrument to prevent the heterogeneous development of national patent laws affecting the free movement of products in the internal market. The duration of the protection granted by the patent may be extended to additional 5 years, by a supplementary protection certificate, granted, under same conditions provided by the regulation, by each Member State. The Community regulations created a legal form of a new national sui generis right, belonging both to the intellectual property right, namely patent right, and the administrative right of the marketing authorization. The main objective of the paper consists in informing the Romanian specialists in the field about the latest evolutions in intellectual property rights, especially in protection of the inventions, as a consequence of Romania’s accession to the European Community.